2009
DOI: 10.3201/eid1511.091147
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter EuroTravNet/GeoSentinel Study of Travel-related Infectious Diseases in Europe

Abstract: We analyzed prospective data on 17,228 European patients who sought treatment at GeoSentinel sites from 1997 to 2007. Gastrointestinal illness (particularly in tourists), fever (those visiting friends and relatives [VFRs]), and skin disorders (in tourists) were the most common reasons for seeking medical care. Diagnoses varied by country of origin, region visited, or categories of travelers. VFRs who returned from sub-Saharan Africa and Indian Ocean islands were more likely to experience falciparum malaria tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
77
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(83 citation statements)
references
References 37 publications
4
77
0
2
Order By: Relevance
“…Consequently, no exact calculations on relative risk could be provided by this study. However, in contrast to the other studies using large numbers of patients, which were multicentric, [9][10][11][12][13][14][15][16][17] this study provides uniformity in patient referral patterns, consistency in coding of diagnoses by clinicians, and central laboratory reference facilities. [22][23][24][25][26][27] As all patients were subject of the same standardized process, maximal comparability of the data was possible in this comparative prevalence study.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Consequently, no exact calculations on relative risk could be provided by this study. However, in contrast to the other studies using large numbers of patients, which were multicentric, [9][10][11][12][13][14][15][16][17] this study provides uniformity in patient referral patterns, consistency in coding of diagnoses by clinicians, and central laboratory reference facilities. [22][23][24][25][26][27] As all patients were subject of the same standardized process, maximal comparability of the data was possible in this comparative prevalence study.…”
Section: Discussionmentioning
confidence: 86%
“…9,10 Several studies have shown that the most prevalent symptoms among travelers and immigrants were diarrhea, fever, and skin disorders. 6,11,[18][19][20] In some studies that compared travelers with immigrants whose purpose of travel was VFR, the risk of acute diarrhea was higher among travelers, whereas the risk for malaria and viral hepatitis was higher among VFRs. 21 The findings mentioned above were considered when patients consulted the Department of Infectious Diseases and Tropical Medicine (DITM) of the University of Munich, Germany.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mobile phones, particularly mobile internet use, facilitate the availability of real-time information at any time and nearly anywhere in the world to the general public and may be useful in this context [4]. Surveillance could also be operated through specialised networks reporting on travelassociated diseases, including GeoSentinel [40] and EuroTravnet [41]; however participation to large scale open air festival and MGs is not documented specifically at the moment in these databases.…”
Section: Discussionmentioning
confidence: 99%
“…[32][33][34] According to the GeoSentinel surveillance network database, the risk for acquiring malaria per region visited was higher in sub-Saharan Africa followed by Oceania, South Asia, Central America, Southeast Asia and South America. 35 Analysis of malaria imported into eight European countries from the Indian subcontinent, led to a consensus statement by the TropNet group recommending that non-selective prescription of prophylaxis for visitors to India, Pakistan, Bangladesh, and Sri Lanka should be dropped.…”
Section: -31mentioning
confidence: 99%